Euphorbia Diterpenes: An Update of Isolation, Structure, Pharmacological Activities and Structure–Activity Relationship - Douglas Kemboi; Xavier Siwe-Noundou; Rui W. M. Krause; Moses K. Langat; Vuyelwa Jacqueline Tembu (Molecules, 2021)
Euphorbia species have a rich history of ethnomedicinal use and ethnopharmacological applications in drug discovery. This is due to the presence of a wide range of diterpenes exhibiting great structural diversity and pharmacological activities. As a result, Euphorbia diterpenes have remained the focus of drug discovery investigations from natural products. The current review documents over 350 diterpenes, isolated from Euphorbia species, their structures, classification, biosynthetic pathways, and their structure–activity relationships for the period covering 2013–2020. Among the isolated diterpenes, over 20 skeletal structures were identified. Lathyrane, jatrophane, ingenane, ingenol, and ingol were identified as the major diterpenes in most Euphorbia species. Most of the isolated diterpenes were evaluated for their cytotoxicity activities, multidrug resistance abilities, and inhibitory activities in vitro, and reported good activities with significant half-inhibitory concentration (IC50) values ranging from 10–50 µM. The lathyranes, isopimaranes, and jatrophanes diterpenes were further found to show potent inhibition of P-glycoprotein, which is known to confer drug resistance abilities in cells leading to decreased cytotoxic effects. Structure–activity relationship (SAR) studies revealed the significance of a free hydroxyl group at position C-3 in enhancing the anticancer and anti-inflammatory activities and the negative effect it has in position C-2. Esterification of this functionality, in selected diterpenes, was found to enhance these activities. Thus, Euphorbia diterpenes offer a valuable source of lead compounds that could be investigated further as potential candidates for drug discovery.